Nursing Practice Based on Evidence-Based Concepts to Prevent Enteral Nutrition Complications for Critically Ill Neurosurgical Patients - Jiao, Jia; Chen, Yu; Yang, Lijian; Li, Wei; Zhou, Zhiwei; Li, Lan; Xiao, Yinghong; Zhao, Jiasha; Li, Linzhi; Xia, You (Frontiers in Surgery, 2022)
Purpose: To explore the practical value of enteral nutrition care guided by evidence-based concepts in preventing enteral nutrition complications in neurosurgical critically ill patients. Methods: Three hundred critically ill patients from March 2020 to October 2021 in our neurosurgery department were included in the study. Patients were divided into a control group and a study group according to the order of their admission. The control group received conventional enteral nutrition care, and the study group received enteral nutrition care based on evidence-based concept guidance. The levels of serum nutritional indicators feeding compliance rate, incidence of complications and prognosis during the observation period were compared between the two groups. The scores of the Questionnaire of Knowledge, Attitude and Practice on Nutrition among Neurosurgical Nurses before and after the implementation of evidence-based care were compared among nursing staff in the study group. Results: At 1 and 2 weeks after enrollment, Hb, ALB, and TP levels were lower in both groups than before enrollment in the same group (P<0.05). At 2 weeks after enrollment, Hb, ALB, and TP levels were higher in both groups than at 1 week after enrollment in the same group (P<0.05). At 1 and 2 weeks after enrollment, Hb, ALB, and TP levels were higher in the study group than in the control group (P<0.05). At 7 days after feeding, the feeding compliance rate was higher in the study group (94.67%) than in the control group (70.00%) (P<0.05). The total complication rate was lower in the study group (8.00%) than in the control group (16.00%) (P<0.05). The percentage of good prognosis was higher in the study group (34.00%) than in the control group (23.33%) (P<0.05). After the implementation of evidence-based care, caregivers in the study group scored higher on nutrition knowledge, nutrition attitudes, and nutrition practices than before the implementation (P<0.05). Conclusion: The implementation of evidence-based nursing interventions in neurosurgical critically ill patients based on evidence-based concepts is of great clinical value in correcting their nutritional status, preventing enteral nutritional complications, improving prognosis, and enhancing the nutritional knowledge, attitudes and practices of nursing staff.